Exploring the Application of a Multicenter Study Design in the Preclinical Phase of Translational Research - Hunniford, Victoria (Université d'Ottawa / University of Ottawa, 2020)
Multicenter preclinical studies have been suggested as a method to improve potential clinical translation of preclinical work by testing reproducibility and generalizability of findings. In these studies, multiple independent laboratories collaboratively conduct a research experiment using a shared protocol. The use of a multicenter design in preclinical experimentation is a recent approach and only a handful of these studies have been published. In this thesis, I aimed to provide insight into preclinical multicenter studies by 1) systematically synthesizing all published preclinical multicenter studies; and 2) exploring the experiences of, barriers and enablers to, and the extent of collaboration within preclinical multicenter studies. In Part One, I conducted a systematic review of preclinical multicenter studies. The database searches identified 3150 citations and 13 studies met inclusion criteria. The multicenter design was applied across a diverse range of diseases including stroke, heart attack, and traumatic brain injury. The median number of centers was 4 (range 2-6) and the median sample size was 133 (range 23-384). Most studies had lower risk of bias and higher completeness of reporting than typically seen in single-centered studies. Only five of the thirteen studies produced results consistent with previous single-center studies, highlighting a central concern of preclinical research: irreproducibility and poor generalizability of findings from single laboratories. In Part Two, I performed semi-structured interviews with researchers who have been involved in a preclinical multicenter study. Braun and Clarkes’ thematic analysis was used to identify emerging themes, and the extent of collaboration was evaluated using an established theory of collaboration developed by Wood and Gray. Twelve researchers from 6 studies were interviewed. Most participants indicated that funding and the culture of the scientific community were barriers, and that established relationships and transparency with collaborators were enablers to multicenter studies. Some participants felt that a harmonized protocol was optimal, while others stated that variability in the protocol across sites was more appropriate. Most participants indicated that multicenter studies had a purpose and place in preclinical research. My findings also suggest that multicenter preclinical studies may provide a method to robustly assess therapies prior to considering clinical translation. These insights will allow for more effective planning and execution of future preclinical multicenter projects and may support the development of best practices and guidelines.
Keywords: Preclinical research; Multicenter studies; Translation; Systematic review; Interview study